2015
DOI: 10.1155/2015/548031
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of a Combined Thiourea and Hexamethylenetetramine as Inhibitors for Corrosion of N80 in 15% HCl Solution: Electrochemical Experiments and Quantum Chemical Calculation

Abstract: The inhibition mechanism of thiourea (TU) and hexamethylenetetramine (HMTA) mixed in 15% HCl solution on N80 surface was investigated by potentiodynamic polarization, electrochemical impedance spectroscopy measurements, and surface morphology analysis. Quantum chemical calculations and molecular dynamics simulations were performed to study the properties of TU and HMTA. The results showed that the inhibitors can form strong bonds and stable films on the surface, which inhibits the cathodic and anodic reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Mulliken charge distributions analysis is widely used for the prediction of the adsorption center of inhibitors. The data in Table S1 manifests that the most negative atomic charges happen to the N or O atomic for the three molecules, indicating adsorption centers being N and O atoms [27,28]. According to the frontier molecular orbital theory, the formation of a transition state occurs due to interactions between the frontiers orbitals (HOMO and LUMO) of the reactants [29].…”
Section: Resultsmentioning
confidence: 98%
“…Mulliken charge distributions analysis is widely used for the prediction of the adsorption center of inhibitors. The data in Table S1 manifests that the most negative atomic charges happen to the N or O atomic for the three molecules, indicating adsorption centers being N and O atoms [27,28]. According to the frontier molecular orbital theory, the formation of a transition state occurs due to interactions between the frontiers orbitals (HOMO and LUMO) of the reactants [29].…”
Section: Resultsmentioning
confidence: 98%
“…This result was supported by the modulus plot in Figure 11c, in which the absolute impedance of the The Bode plot (Figure 11b) illustrates that the phase angle of the blank system was in the range of 35 • to 38 • with the resistive behavior, while that of the cysteine-inhibited system was in the range of 50 • to 52 • , reflecting the capacitive behavior. The increase in the phase angle suggested that cysteine forms a passive film on the metal surface, hindering the interaction with corrosive species [31]. The change in rotational speed from static to dynamic conditions did not cause much variation in the phase angle.…”
Section: Effect Of Flow Conditionmentioning
confidence: 92%
“…Furthermore, the inhibitor film reduced the Q f from 1234.50 ± 14.50 µF/cm 2 in the blank system to 312.21 ± 16.24 µF/cm 2 in the 500 ppm cysteine system. This may have resulted from the thickening of an inhibitor film and the effective integration with the double layer [31].…”
Section: Effect Of Cysteine Concentrationmentioning
confidence: 99%
“…All specimens were manually polished by metallographic emery papers with a grit size from 400 to 800, 1000, and 1200. Afterward, they were immersed in petroleum ether for 10 min, washed thoroughly with distilled water, degreased with acetone, washed again with bidistilled water, and ultimately dried at room temperature [19].…”
Section: Methodsmentioning
confidence: 99%